(Counter-)Imperial Mode of Living and Surviving: contextualizations from South America - Dorn, Felix Malte; Hafner, Robert; Ruiz Peyré, Fernando; Krapovickas, Julieta (DIE ERDE – Journal of the Geographical Society of Berlin, 2022)
The notion of the imperial mode of living (IML) has been widely taken up in both academic, activist and sociopolitical contexts. More recently, scholars have begun to explore the concept not only theoretically, but also empirically, dealing with how the IML works in practice. We see great potential for human geography to ground the IML. To do so, in this article we introduce a set of five geographical cornerstones on the IML, stating that (1) the IML demonstrates that capitalism requires a non-capitalist outside, (2) the IML relies on infrastructural colonialism constituted by global value chains, (3) the IML is tied to current notions of development, (4) the critique of the IML concept challenges the patriarchal order and that (5) the IML conditions a counter-imperial mode of living. Reflecting on soybean cultivation, transhumance and lithium mining in South America, we show that grounding the IML not only requires a critical analysis of the dominant power relations, but also a consideration of opposing tendencies. In this context, we observe that a reproduction of global discourses inherent to the IML often leads to an ‘imperial mode of surviving’ locally. In contrast, we understand protest movements and conflicts as a ‘counter-imperial mode of living’.